2019
DOI: 10.5539/jel.v8n1p220
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Vocational Motivations of Physical Education and Sports Teachers in Terms of Some Variances

Abstract: The aim of this study is to examine the professional motivations of Physical Education and Sports Teachers. The study group included totally (n=300) 93 female and 207 male physical education and sports teachers working in; Erzurum (n=30), Yozgat (n=22), Kayseri (n=30), Nevsehir (n=56), Aksaray (n=22), Ankara (n=52), Istanbul (n=44) and Kirsehir (n=40) provinces. The research was made in 2017–2018 academic year. As a data collection tool “Vocational Motivation Scale”, which consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As research on job demand/resource and worker motivation has shown that without sufficient external rewards as necessary resources, worker intrinsic motivation cannot be sustained for long. Most physical education teachers in Turkey explicitly expressed that working for financial compensation motivates them (Var & Yildiz, 2019) and most of the best teachers in the United States cited the same reason as the motivation to acquire the National Board Certification (Woods & Rhoades, 2010). Therefore, solely relying on strategies promoting intrinsic motivation may be unrealistic.…”
Section: Theoretical Pitfalls Of the Sole Intrinsic Motivation Perspe...mentioning
confidence: 99%
See 3 more Smart Citations
“…As research on job demand/resource and worker motivation has shown that without sufficient external rewards as necessary resources, worker intrinsic motivation cannot be sustained for long. Most physical education teachers in Turkey explicitly expressed that working for financial compensation motivates them (Var & Yildiz, 2019) and most of the best teachers in the United States cited the same reason as the motivation to acquire the National Board Certification (Woods & Rhoades, 2010). Therefore, solely relying on strategies promoting intrinsic motivation may be unrealistic.…”
Section: Theoretical Pitfalls Of the Sole Intrinsic Motivation Perspe...mentioning
confidence: 99%
“…Extrinsic motivation refers to motivation in which an individual engages in an activity due to the controlling effects of external factors such as receiving tangible or symbolic rewards or complying with an external contingency imposed by those in control (Ryan & Deci, 2000). As illustrated in the review, physical education teachers do value extrinsic rewards as a source of motivation (Woods & Rhoades, 2010) as much as they value the intrinsic value of teaching (Carson & Chase, 2009; Var & Yildiz, 2019; Woods & Rhoades, 2010).…”
Section: Reconceptualising Teacher Motivation Researchmentioning
confidence: 99%
See 2 more Smart Citations